Do Nickel and Iron catalyst nanoparticles affect the mechanical strength of carbon nanotubes?. (April 2018) - Ostadhossein, Alireza; Yoon, Kichul; van Duin, Adri C.T.; Seo, Jin Won; Seveno, David
Abstract: The growth of carbon nanotubes (CNTs) is strongly mediated by the interaction between Carbon atoms and catalyst nanoparticles, in particular in processes like chemical vapor deposition or floating method. However, the effects these nanoparticles on the mechanical strength of the grown CNTs have remained elusive. Using molecular dynamics dynamic simulations via ReaxFF force fields, the interactions between defect-free single wall CNTs and a series of Nickel (Ni) and Iron (Fe) nanoparticles (NPs) are studied. Pure metal NPs significantly reduce the strength of the CNTs whereas oxidized NPs have more limited detrimental effects. For the same Oxygen content, we also observe that the Fe oxide NPs weaken C–C bonds, i.e. CNTs grown in the presence of Ni particles have higher mechanical strength comparing to those obtained from Fe-based nanoparticles. An analysis of the formation and dissociation of chemical bonds between the C, O, Ni and Fe atoms together with the stress analysis during tensile tests also enable us to elucidate the role of the NPs on the failure mechanisms. The C–C bonds interacting directly with Ni atoms are weakened and therefore control the failure of the CNTs. Surprisingly, the failure of the same CNTs in contact with Fe nanoparticles is driven by the weakening of C–C bonds not directly bonded to Fe atoms.